2023
DOI: 10.3390/v15010176
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating T Cells in EBV-Associated Gastric Carcinomas Exhibit High Levels of Multiple Markers of Activation, Effector Gene Expression, and Exhaustion

Abstract: Epstein–Barr virus (EBV) is a gamma-herpesvirus associated with 10% of all gastric cancers (GCs) and 1.5% of all human cancers. EBV-associated GCs (EBVaGCs) are pathologically and clinically distinct entities from EBV-negative GCs (EBVnGCs), with EBVaGCs exhibiting differential molecular pathology, treatment response, and patient prognosis. However, the tumor immune landscape of EBVaGC has not been well explored. In this study, a systemic and comprehensive analysis of gene expression and immune landscape featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 90 publications
(125 reference statements)
2
8
0
Order By: Relevance
“…In particular, EBVaGCs are "immune hot" tumors with higher levels of MHC I and II expression and cytotoxic T cell infiltration and activation when compared to EBVnGCs. [12,13,15,16,47]. Due to their unique immune features, understanding how EBVaGCs differ in relation to EBVnGCs may help elucidate the underlying mechanisms of EBV-mediated changes in the tumor immune landscape and may eventually result in better treatment options for EBVaGC patients.…”
Section: The Correlation Of Gene Expression Levels With Immune Landsc...mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, EBVaGCs are "immune hot" tumors with higher levels of MHC I and II expression and cytotoxic T cell infiltration and activation when compared to EBVnGCs. [12,13,15,16,47]. Due to their unique immune features, understanding how EBVaGCs differ in relation to EBVnGCs may help elucidate the underlying mechanisms of EBV-mediated changes in the tumor immune landscape and may eventually result in better treatment options for EBVaGC patients.…”
Section: The Correlation Of Gene Expression Levels With Immune Landsc...mentioning
confidence: 99%
“…It is estimated that EBV is the causative agent of around 10% of all gastric cancer (GC) cases worldwide, though relative proportions differ by region [10,11]. Furthermore, EBVaGCs are molecularly and pathologically distinct entities from EBV-negative GCs (EBVnGCs), with higher survival rates, male-dominant incidence, genome-wide promoter hypermethylation, increased T cell infiltration, as well as higher levels of MHC-I and MHC-II expression [12][13][14][15][16]. Additionally, several EBV-associated proteins and 44 miRNAs originating from the Bam-HI A rightward transcripts (miR-BARTs) are consistently expressed in EBVaGCs, likely contributing to the oncogenesis and progression of EBVaGCs [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, additional sequencing of TCGA GC tissue samples have yielded datasets for expression levels of EBV-encoded mRNAs ( 201 ) and miRNAs ( 87 ), compilation of immune landscape features ( 298 ), and standardized patient outcome data ( 299 ). As one example of the utility of this data, bioinformatic comparisons confirmed that the EBVaGC TME exhibits many aspects of a T cell-inflamed phenotype, with greater T and NK cell infiltration, increased expression of many immune checkpoint markers (BTLA, CD96, CTLA4, LAG3, PD1, TIGIT and TIM3), and multiple T cell effector molecules in comparison with EBVnGCs ( 300 ).…”
Section: Datasets and Tools In Ebvagcmentioning
confidence: 90%
“…Post-2020, propelled by technological advancements, breakthroughs such as the use of single-cell RNA sequencing in GC cells and transcriptome analysis of peritoneal cancer samples from patients with GAC have emerged, enriching our understanding of tumor biology and uncovering novel immunotherapy targets[ 111 , 112 ]. Notably, EBV-positive status has been identified as a potential biomarker for EBV-associated GC, paving the way for future studies[ 113 ].…”
Section: Discussionmentioning
confidence: 99%